Deformation state extraction from electron backscatter diffraction patterns via simulation-based pattern-matching. (1st January 2021) - Kurniawan, Christian; Zhu, Chaoyi; DeGraef, Marc
Graphical abstract: Abstract: A new simulation-based pattern-matching method is developed to retrieve the deformation tensor from electron backscatter diffraction patterns. Minimizing the least-squares difference between a target pattern and simulated deformed patterns, the deformation state of the target pattern can be inferred with an average absolute error of ∼ 10 − 8 for the distortion tensor under ideal conditions. The new approach is robust against significant pattern rotation compared to the cross-correlation based method. Additionally, the pattern center can be simultaneously optimized with an average absolute distortion tensor error of ∼ 10 − 4 for noise-free patterns.